Bilateral talocalcaneal tarsal coalition with flatfeet treated with single-stage coalition resection and calcaneal lengthening osteotomy: A case report - Alabdulkareem, Abdulrahman I.; Alkhalife, Yasser I.; Bayounis, Abdulaziz M.; Shabib, Abdullah A. B.; Alrogy, Waleed A.; Al-Jahdali, Fares H.; Alsayegh, Samir O. (Journal of Musculoskeletal Surgery and Research)
A coalition is a bridge connecting osseous structures. Tarsal coalitions typically involve talocalcaneal and calcaneonavicular joints. As a result, patients might present with pain and/or rigid flatfoot deformity. We outline a case of bilateral middle facets talocalcaneal tarsal coalition with rigid flatfeet who was treated with resection combined with flatfoot reconstruction. the patient was an 11-year-old Saudi girl who had progressive bilateral flatfoot for which non-operative treatment failed. A single-stage middle facet talocalcaneal coalition resection with concomitant Evans calcaneal lengthening osteotomy and gastrocnemius recession was performed. Postoperatively, the American Orthopaedic Foot and Ankle Society (AOFAS) ankle midfoot score was measured, and the patient had a score of 90/100. The outcome was satisfactory, and the other foot was operated on 6 months later, with the same procedure and outcome (AOFAS: 90/100). Six years of follow-up showed no recurrence and a satisfactory lifestyle with no activity limitation. We aimed to highlight the AOFAS score 6 years after resecting the coalitions while reconstructing the foot in a single-staged procedure.